BUDAYA ORGANISASI PADA KALANGAN PEGAWAI PEREMPUAN DI DINAS TENAGA KERJA DAN TRANSMIGRASI DAERAH PROVINSI SULAWESI UTARA - Heidy Mariani Veronica Rumondor; Maria H. Pratiknjo; Leviane J. H. Lotulung (Sam Ratulangi University, 2021)
This study aims to analyze the organizational culture of women in the Regional Manpower and Transmigration Office of North Sulawesi Province. This research uses descriptive qualitative research method. Data collection is done by interview, documentation and observation. Furthermore, the data is analyzed by reducing the data, presenting the data and drawing conclusions. The results showed that the organizational culture among female employees at the Regional Manpower and Transmigration Office of North Sulawesi Province could be said to be running well in accordance with the predetermined vision and mission. In carrying out organizational culture, there are obstacles faced, namely the occurrence of leadership changes, the existence of other organizations in the organization and the occurrence of crises in the organization. Given these obstacles, organizations must strive to improve quality, namely by continuing to innovate by daring to take risks, paying attention to small things in an organization that is results-oriented and people-oriented as the effect of the results obtained on the members of the organization and the team. and being aggressive and competitive within the organization.